(untitled) (The Journal of Plant Protection Sciences, 2024)
Pulses are important source of plant protein in many developing countries of the tropics and sub-tropics and considered as the second most important group of crops worldwide. Glob ally, 840 million people are undernourished mainly on account of inadequate intake of proteins, vitamins and minerals in their diets. Out of total 12.6 million tons, 5.5% is lost due to the non-availability of proper storage facili ties with the farmers and vulnerability of pulses to stored grain pests (4) which inflict severe losses mainly in the storage. Among the storage pests, bruchids particularly the pulse beetle, Callosobruchus chinensis L. in cur greater importance as the pest having cos mopolitan distribution and causing serious damage to pulses from the field (5).